Assessment of relationship between post-injection plume migration and leakage risks at geologic CO2 storage sites. (October 2020) - Pawar, Rajesh J.; Chu, Shaoping; Makedonska, Nataliia; Onishi, Tsubasa; Harp, Dylan
Highlights: Evolution of injected CO2 plume and reservoir pressure in CO2 storage reservoir is a complex function of reservoir heterogeneity, flow dynamics and injection conditions. Complex migration of injected CO2 in the reservoir can be captured effectively using newly developed metrics for complex shaped CO2 plumes. Time-dependent behavior of CO2 and pressure plume metrics can be used to determine effective post-injection site care plan including monitoring duration and frequency. Continued evolution and migration of CO2 plume in the reservoir during post-injection phase does not necessarily imply non-endangerment of groundwater aquifer. Abstract: We performed a numerical modeling study focused on the relationship between post-injection plume migration and leakage risks at geologic CO2 storage sites. We use the model for Rock Springs Uplift in southwestern Wyoming as our hypothetical case study. We performed multiple sets of reservoir simulations, each with 29 equi-probable realizations of reservoir permeability heterogeneity, simulating different injection scenarios. Three different CO2 injection rates and an open and compartmentalized reservoir are evaluated. We applied newly developed moment-based plume mobility metrics to characterize migration and evolution of injected CO2 plume. We applied the integrated assessment model developed by the National Risk Assessment Partnership (NRAP-IAM-CS) using the results of reservoir simulations of CO2 and overpressure to quantify potential CO2 and brine leakage through wells and resulting groundwater aquifer impacts. The plume mobility metrics provide detailed analyses of the effect of reservoir permeability heterogeneity, CO2 injection rate, and compartmentalization on CO2 plume and overpressure areas, velocities, and spreading. Based on leakage risk assessment our results indicate that lack of injected CO2 plume stability (or non-zero plume mobility) may not directly imply groundwater aquifer endangerment and the leakage risks are dependent on multiple factors beyond CO2 plume stability including presence of wells and their locations and types.